Outcome of Varus Derotation Osteotomy for Containment of Femoral Head in Advanced Perthes Disease (Journal of Enam Medical College, 2021)
Background: Legg-Calve-Perthes (LCP) disease, or idiopathic avascular necrosis of the femoral head occurs during early childhood and is caused by impaired circulation in the femoral head. Varus derotation osteotomy (VDO) was described over half a century ago, and is now a popular method for the operative treatment of Perthes disease.Objective: To find out the clinical and radiological outcome of varus derotation osteotomy for containment of femoral head in advanced Perthes disease.Materials and Methods: This observational study was conducted in the Department of Orthopaedic Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from March 2015 to September 2017. Total 20 cases of advanced Perthes disease were enrolled. Pre- and post-operative period were evaluated by interview and clinical examination by using a semi-structured questionnaire. Demographic and clinical information were recorded. All patients had a pre- and post-operative x-rays. We used visual analog scales (VAS) for scoring pain; Wiberg’s central edge angle, epiphyseal extraction index, neck shaft angle and Larson (Iowa) hip score were used to assess the outcome of VDO. Comparison of continuous variables between the two groups was made with Student’s t-tests. Comparison of proportions between Herring groups B and C were made with chi-square tests. p